Утицај времена сузбијања корова на раст и принос горњег пиринча (Ориза сатива Л.) - Adigun, Joseph; Kolo, Emmanuel; Daramola, Olumide; Adeyemi, Olusegun; Bodunde, Jacob (Journal of Agricultural Sciences (Belgrade), 2021)
Weed interference is a major threat to rice production, leading to high yield reduction and reduced profitability. Field experiments were therefore conducted to evaluate the effect of different timing of weed control on growth and yield of upland rice in 2015 and 2016 cropping seasons. The treatments consisted of periods when the crop was allowed to be weed-infested for the first 3, 6 and 9 weeks after sowing (WAS), and periods when the weeds were controlled for the first 3, 6 and 9 WAS. Two treatments of weed infestation and weed control till harvest were also included as the checks in a randomized complete block design with three replications. In both years, rice grain yields ranged from 0.6-0.8 t ha -1 in plots kept weed-infested till harvest to 3.5-3.9 t ha -1 in plots kept weed-free till harvest, indicating a 79-83% yield loss with uncontrolled weed growth. Weed infestation for the first 3 WAS did not cause significant reduction on growth and yield of rice provided the weeds were removed thereafter. Delay in weed control until 9 WAS, however, reduced rice growth and resulted in irrevocable yield reduction. For optimum grain yield it was only necessary to remove the weeds between 3 and 9 WAS, as no significant yield increase was observed from weed control after 9 WAS in both years. This study showed that weed control between 3 and 9 WAS will give optimum growth and yield of upland rice.